Bridging the Gap: Examining Humor Dynamics Between Secondary School Educators and Students - Angela Putri Natalia; Ounu Zakiy Sukaton; Melany Melany (Journal of English Language Studies, 2024)
The utilization of humor in foreign language classrooms has demonstrated positive impacts in terms of memory retention, information processing performance, and students’ positive perception of their teachers While numerous studies have explored humor in education, there's a gap in understanding the differences in humor usage between educators and students within the same classroom context. Addressing this gap can illuminate the dynamics of teacher-student relationships, classroom atmosphere, and student engagement, informing pedagogical practices and enhancing the overall instructional experience. This study aims to explore prevalent types of humor in classrooms, focusing on distinct patterns exhibited by educators and students, and uncovering underlying dynamics to enrich our understanding of humor's role in education. We worked with 27 students from SMPK Bhakti Luhur Malang and data collection involved the use of audio recordings of classroom interactions between students and teachers. Throughout our data, we found that humor is useful as a coping mechanism, a tool in relationship building, and a tool for managing class among others. We also illustrated how teachers and students used different ranges of humor types for different purposes, yet still maintaining a positive class dynamic. We hope that our findings will contribute to further enhancing the use of humor in educational settings.